Molecular phylogenetics of Pterocyclus (Apiaceae) based on nrDNA ITS sequences: revised circumscription with a restored species - Zhou, Jing; Wei, Jin; Niu, Junmei; Liu, Xiaoli; Liu, Zhenwen (Phytotaxa, 2021)
The genus Pterocyclus Klotzsch, along with many others, constituted the taxonomically complex Pleurospermum s.l. To delimit its circumscription and clarify its interspecific relationships, molecular phylogenetic analysis and detailed specimen examination were carried out. Its status as an independent genus was confirmed, with four species recognized. Pterocyclus wolffianus, the synonymous species of Pterocyclus forrsetii should be restored as an independent species. A new taxonomic account for Pterocyclus and an identification key to its four species, are provided.